Bridging the Gap Between Management-Organizational Research and Public Policy - Dutton, Jane E. (Academy of Management Journal, 2005)
The article discusses four initiatives that could help bridge the gap between management-organizational scholarship and public policy. First, the author suggests enriching research distribution channels, arguing that traditional avenues for publishing are a more valuable means for distributing research to a specialized group of academics and practitioners than they are for reaching public policy makers. Second, she recommends that incentives be created to encourage contributions to public policy knowledge and debate. Third, the author advocates the creation of social networks linking researchers and public policy makers. Lastly, she asserts that doctoral education should place a greater emphasis on public policy issues.